ANALISA PENYEBAB DAN AKIBAT PERUBAHAN KONTRAK PEKERJAAN (CONTRACT CHANGE ORDER) TERHADAP BIAYA PADA PROYEK TRANSMISI - Diah Margareta; Ani Firda; Yasmid Yasmid (FORUM MEKANIKA, 2016)
Thisresearch was motivated by a lot of demands of contract change order addendum in the relatedagency. From this research, researcher was expected to be able to describe the elements of main cause ofcontract change order and impact on the contract cost. The method used in this research wasStatisticsDescriptive for describing the questionnaire results, whereas the calculation of the new value of contractwasusing the unit price calculation analysis. Sources of data in this research were 8 people consisting of projectowners and contractor. Basedon the results of the main causes of contract change order, it was found that themain cause of contract change order was the location change of the project resulting from transmission linesthrough the region of coal mining, the main party that influenced the contract change order was the owner ofthe project, The implementation phase of contract change order was mid-contract work, the stages leading tocontract change order was land acquisition and the impact of contract change order in the cost was thedecrease of contract value from the initial contract.